STUDY OF CRYSTAL STRUCTURE AND BAND GAP ENERGY OF ZnO NANOPARTICLES USING TAUC PLOT METHOD FROM ABSORBANCE CURVES: STUDI STRUKTUR KRISTAL DAN CELAH PITA ENERGI NANOPARTIKEL ZnO MENGGUNAKAN METODE TAUC PLOT DARI KURVA ABSORBANSI - Annete Gabriella Nuraliya; Iwan Sugihartono; Osi Arutanti; Maykel Manawan (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
ZnO nanoparticles have been successfully synthesized using the precipitation method with a low acidity level (pH 9) with an annealing process at 400 °C for 2 hours. ZnO nanoparticles were characterized using an X-Ray Diffractometer (XRD) and a UV-Vis Spectrophotometer to analyze the crystal structure and absorbance capability of the ZnO nanoparticles in the wavelength range of 200-700 nm. Based on the Inorganic Crystal Structure Database (ICSD) number #01-079-0207, the X-Ray Diffraction (XRD) pattern of ZnO nanoparticles has a Hexagonal Wurtzite structure with the space group p63mc. The results of the UV-Vis characterization show the presence of absorbance with the highest intensity at a wavelength of 340 nm. Next, the determination of the energy gap of ZnO nanoparticles was carried out using the Tauc Plot method from the absorbance curve. Based on the Tauc Plot results, the energy band gap of ZnO nanoparticles is 3.07 eV.